"No One Ever Asked Me": Urban African American Students' Perceptions of Educational Resilience. Issue 1 (January 2014) - Williams, Joseph M.; Portman, Tarrell Awe Agahe
<x xml:space="preserve">Abstract</x> This qualitative study examined high‐achieving urban African American high school graduates' (N = 5) retrospective appraisal of what K–12 students from high‐risk urban areas need to succeed academically despite seemingly insurmountable social, financial, and educational barriers. Findings revealed 6 themes: shared responsibility for educational outcomes, being a part of the solution, parental involvement by any means, natural support systems, school counselors as change agents, and community collaboration to raise a scholar. Recommendations for school counselors are discussed. Este estudio cualitativo examinó la opinión retrospectiva de un grupo de graduados Afroamericanos urbanos de alto nivel académico en educación secundaria (N = 5) sobre lo que necesitan los estudiantes de K–12 en áreas urbanas de alto riesgo para tener éxito académico a pesar de las barreras sociales, económicas y educativas aparentemente infranqueables. Los hallazgos revelaron 6 temas: responsabilidad compartida por los resultados educativos, ser parte de la solución, implicación de los padres en cualquier modo posible, sistemas naturales de apoyo, consejeros escolares como agentes de cambio, y colaboración comunitaria para educar a un individuo estudioso. Se discuten recomendaciones para los consejeros escolares.